(untitled) (Journal of Forest and Natural Resource Management, 2025)
Ecotourism is promoted as a strategy for sustainable rural development, specifically in those regions that are rich in biodiversity. The Panchase region of Nepal is rich in biodiversity and ecotourism. The impacts of ecotourism activities in such region are still unknown; therefore, this study aims to assess the socioeconomic impacts of community-based ecotourism in this forest area. This study employed a mixed-methods approach, that integrate household surveys (n=48), focus group discussions (n=4), and key informant interviews (n=7) and both descriptive and inferential statistics were used to analyze the data. The findings reveal that community-based ecotourism is a significant livelihood driver of homestay owners who relying on it as a primary income source and creating employment opportunity. The study documented an overwhelming consensus on socioeconomic benefits like improved access to education, strengthened social cohesion and cultural preservation. Similarly, almost all the respondent agreed on the role of ecotourism on conservation awareness and biodiversity conservation. However, challenges like lack of marketing, unequal distribution of resources, and the isolation of stakeholders still exist. Long-term sustainability of ecotourism demands a clear strategy that ensures equitable benefit sharing, strengthens collaborative governance, and actively involves youth is essential to balance economic development with environmental preservation.